A Content and Comparative Analysis of Job Advertisements for Special Collections Professionals Using ACRL RBMS Guidelines. Issue 6 (17th August 2020) - Warren, Kellee E.; Scoulas, Jung Mi
Abstract: Despite a plethora of job advertisement analyses in librarianship, few studies examine advertisements for skilled special collections professionals in public services. This study analyzed job advertisements for special collections professionals in public services in 2017–2019 to understand the extent to which duties go beyond reference, instruction, and outreach. In many cases, academic librarianship requires one to manage librarianship responsibilities alongside scholarship demands, and this article reveals how expanding responsibilities may generate work–work conflict leading to burnout.